Impact of Mobile Technologies on Cervical Cancer Screening Practices in Lagos, Nigeria (mHealth-Cervix): A Randomized Controlled Trial. (2021) - Okunade, Kehinde S.; Soibi-Harry, Adaiah; John-Olabode, Sarah; Adejimi, Adebola A.; Allsop, Matthew J.; Onyeka, Tonia C.; Akaba, Godwin O.; Oshodi, Yusuf A.; Salako, Omolola; Ugwu, Aloy O.; Adefemi, Ayodeji; Anorlu, Rose I.; et al.
Abstract : PURPOSE: We assessed the impact of mHealth on Pap test screening uptake and also determined the factors that affect screening uptake among women in Lagos, Nigeria. MATERIALS AND METHODS: A randomized controlled trial was carried out among women in two tertiary health institutions in Lagos, Nigeria, between July 2020 and March 2021. Participants were randomly assigned to either a text message (mHealth) intervention or usual care arm. The main study outcome was the uptake of Pap smear testing within 6 months of enrollment in the study. We tested the associations between two groups of continuous variables using the unpooled independent-sample t -test (normal distribution) and that of two groups of categorical variables with the chi-square (χ 2 ) test. Using a multinomial logistic regression model, we adjusted for relevant sociodemographic and clinical predictors of uptake of Pap smear screening. Statistical significance was defined as P < .05. RESULTS: There was a significantly higher rate of uptake of Pap smear screening among women in the mHealth arm compared with those in the usual care arm (51.0% v 35.7%, P = .031). Following adjustment in the final multivariate model, level of income (odds ratio [OR] = 5.13, 95% CI, 1.55 to 16.95), awareness of Pap smear (OR = 16.26; 95% CI, 2.49 to 76.64), General Outpatient clinic attendance, and introduction of mHealth intervention during follow-up (OR = 4.36; 95% CI, 1.44 to 13.22) were the independent predictors of Pap smear uptake. CONCLUSION: The use of mHealth technologies intervention via short-text message services is a feasible solution for cervical cancer prevention in low- and middle-income countries, and thus, the widespread use of mHealth services by health care providers and policymakers could contribute to the implementation of cervical cancer prevention services in Nigeria and in the settings of other low- and middle-income countries.